RETRACTED ARTICLE: Unveiling Iranian courtyard house: the example of Kuy-e Chaharsad-Dastgah (1946–1950) - Sedighi, Mohamad; Gameren, Dick van (Journal of Architecture and Urbanism, 2019)
View retraction statement: Retraction notice to “Unveiling Iranian courtyard house: the example of Kuy-e Chaharsad-Dastgah (1946–1950)” [Journal of Architecture and Urbanism, 43(1), 91-111, 2019].